2017
DOI: 10.1002/adom.201700419
|View full text |Cite
|
Sign up to set email alerts
|

Robust Cesium Lead Halide Perovskite Microcubes for Frequency Upconversion Lasing

Abstract: FETs), [10,11] memristors, [12,13] and nano lasers [14][15][16] because of their unique optical and electronic characteristics. Recently, much research has been carried on the amplified spontaneous emission (ASE) and lasing of perovskite materials because of their tunable bandgap. For examples, Xing et al. have reported lowtemperature solutionprocessed wavelengthtunable perovskites for lasing, [17] and Xiong et al. have reported nearinfrared nanolasers (Q around 1320) based on organic-inor ganic hybrid perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 49 publications
1
51
0
Order By: Relevance
“…In CsPbBr 3 NCs, the ASE threshold typically is limited by the surface fast charge carrier trapping and multiparticle Auger recombination . However, the two‐photon pumped threshold of embedded CsPbBr 3 NCs of CsPbBr 3 ‐in‐Cs 4 PbBr 6 CMDs pump power P = 400 µJ cm −2 is comparable with or lower than many other reported two‐photon pumped CsPbBr 3 NCs or microcrystals (Table S3, Supporting Information) . The low threshold indicates the CsPbBr 3 NCs are well passivated by the Cs 4 PbBr 6 matrix and the Auger recombination may also be restricted in such CsPbBr 3 (dot)‐in‐Cs 4 PbBr 6 (huge thick shell) system.…”
Section: Resultsmentioning
confidence: 59%
“…In CsPbBr 3 NCs, the ASE threshold typically is limited by the surface fast charge carrier trapping and multiparticle Auger recombination . However, the two‐photon pumped threshold of embedded CsPbBr 3 NCs of CsPbBr 3 ‐in‐Cs 4 PbBr 6 CMDs pump power P = 400 µJ cm −2 is comparable with or lower than many other reported two‐photon pumped CsPbBr 3 NCs or microcrystals (Table S3, Supporting Information) . The low threshold indicates the CsPbBr 3 NCs are well passivated by the Cs 4 PbBr 6 matrix and the Auger recombination may also be restricted in such CsPbBr 3 (dot)‐in‐Cs 4 PbBr 6 (huge thick shell) system.…”
Section: Resultsmentioning
confidence: 59%
“…In this section, recent developments of halide perovskite micro‐/nanostructures are discussed according to the structure and morphology dimensionality. The representative works over the past 5 years are summarized in Table 2 and Figure …”
Section: Different Dimensional Metal Halide Perovskites For Lasingmentioning
confidence: 99%
“…Hu et al reported the two‐photon pumped FP cavity lasing with stability and wavelength tunability from the facile solution‐processed CsPbX 3 perovskite microcubes. A low lasing threshold (≈439 µJ·cm −2 ), high‐quality factor (Q ≈ 1150), and robust laser stability of over 10 h under continuous intense laser shots in ambient atmosphere were observed (up to 3.6 × 10 7 excitation cycles) …”
Section: Perovskite Laser Applicationsmentioning
confidence: 99%